KETERIKATAN KARYAWAN DAN KOMPETENSI DALAM MEPENGARUHI KINERJA KARYAWAN PT. GRAMEDIA ASRI MEDIA KEDIRI - Syahputra, Erwin (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH; Vol 1 No 01 (2021): September 2021DO - 10.32503/ammer.v1i01.2263, 2021)
The Influence of Employee Engagement and Competence on Employee Performance at PT. Gramedia Asri Media Kediri. This study aims to determine the effect of employee engagement and competence on employee performance either partially or simultaneously at PT. Gramedia Asri Media Kediri. The sampling technique in this study uses a saturated sampling technique, which is a sampling technique when all members of the population are used as samples. The sample in the study was 30 employees at PT. Gramedia Asri Media Kediri. Data obtained through observation, interviews, literature study, and questionnaires. The data measuring instrument used is the Likert scale. The analysis technique used is validity test, reliability test, classical assumption test, multiple linear regression analysis test, t test and F test. From the research results, employee engagement variable has an effect but is not significant on employee performance variables. The competence variable has a partial and significant influence on the employee performance variable. Simultaneous test results found that employee engagement and competence variables simultaneously affect employee performance variables. It is known from the results of the F test with a sig value of 0.000 (0.000 <0.05) .